The Effect of Celebrity Endorser Toward Purchase Intention: Negative Publicity as Moderator - Yanti Agustina; Retno Tanding Suryandari; Erghana Kanza Kirana (Khazanah Sosial, 2022)
The aim of this study was to examine the effect of celebrity endorsement, consumer engagement, brand loyalty, negative publication, and purchase intention. This study also aims to examine the moderating effect of negative publication on the relationship between celebrity endorsement and purchase intention. The research sample was 200 respondents and it was selected using a nonprobability sampling technique and using a purposive sampling technique with the research sample criteria being people who follow the XXX celebrity Instagram social media account for at least 3 months, are female and have Instagram social media. Data were collected by questionnaire, distributed online, and analyzed using a structural equation model (SEM) with partial least squares (PLS) as the method. The results showed that celebrity endorsement did not have a positive and significant effect on consumer engagement, but had a positive and significant effect on brand loyalty and purchase intention. Consumer engagement and brand loyalty have a positive and significant effect on purchase intention. The moderating effect shows that negative publication has no effect on the relationship between celebrity endorsement and purchase intention.